2021
DOI: 10.3389/fpsyg.2021.747435
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of Current Findings on Quality of Life Domains and a Proposal for Their Inclusion in Clinical Interventions

Abstract: Whilst the assessment of quality of life (QoL) and well-being has burgeoned in the past 50 years, there still remains relatively little research into its treatment in psychology, in spite of the launching of such approaches as positive psychology to widen the ambit of interventions to promote well-being. We posit that there are a number of outstanding QoL areas that could be integrated into standard therapeutic procedures, and that this would this result in an increase in well-being as a therapeutic outcome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 178 publications
(190 reference statements)
0
6
0
1
Order By: Relevance
“…Based on the above and the more recent research of Jones and Drummond 's [15] summary of current findings on quality of life domains, it was expected that some type of division into subjective (affect and cognition) and objective domains would occur. However, it remained of interest to determine which of the identified subjective domains were independent, and which were related and had common underlying processes that were part of a bigger construct.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Based on the above and the more recent research of Jones and Drummond 's [15] summary of current findings on quality of life domains, it was expected that some type of division into subjective (affect and cognition) and objective domains would occur. However, it remained of interest to determine which of the identified subjective domains were independent, and which were related and had common underlying processes that were part of a bigger construct.…”
Section: Introductionmentioning
confidence: 95%
“…An initial pool of facets was generated from the previous exploratory search of empirical studies that reported significant correlations between perceived quality of life and well-being [15]. The identified areas are relationships, work, money, health and leisure, mindfulness, self-esteem, resolution of past life events, mental style, and life management.…”
Section: Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation
“…La calidad de vida es definida por la Organización Mundial de la Salud como la percepción que tiene un individuo de su posición en la vida en el contexto de la cultura y los sistemas de valores en los que vive y en relación con sus metas, expectativas, estándares y preocupaciones (who, 1995). En ese sentido, hay diversos determinantes para que una persona tenga una buena calidad de vida, algunos estos son las relaciones, la economía, el empleo, eventos de vida y la salud (Jones y Drummond, 2021).…”
Section: Estado De Salud Y Calidad De Vida: Determinantesunclassified
“…According to the literature, quality of life consists of four primary life quality domains (e.g., Physical Health, Social Support, Psychological Health, and Vocational/Economic Status) [1,2] to as many as 10 secondary quality of life domains (e.g., Relationships/ Social Support, Work/Vocational Activities, Money/Finances; General Health; Leisure/Recreation; Mindfulness/Self-awareness; Self-Esteem; Major Life Events &/or Life Change; Mental Health/ Coping; Life Management/Goal Setting) depending on the patient population studied and specificity of the research [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%